A study of risk factors for tuberculous meningitis among patients with tuberculosis in China: An analysis of data between 2012 and 2019 - Huang, Mailing; Ma, Yan; Ji, Xinyu; Jiang, Hui; Liu, Fangchao; Chu, Naihui; Li, Qi (Frontiers in Public Health, 2023)
Purpose: We aimed to explore factors associated with increased probability for tuberculous meningitis (TBM) among tuberculosis (TB) patients. Methods: This retrospective study was conducted in Beijing Chest Hospital from January 1, 2012 to December 31, 2019. Demographic and clinical data of TB patients were extracted from electronic medical records using a standardized data collection system. Factors associated with TBM were analyzed using SPSS 19.0 with univariate and multinomial regression models. Results: A total of 22988 cases enrolled in our study, among them, 3.1% were TBM cases including 127 definite and 581 probable TBM, respectively. The multinomial analysis demonstrated that definite TBM was significantly associated with aged < 30 years [adjust odds ratio (aOR)=3.015, 95% confidence interval (CI): (1.451-6.266)], farmer [aOR=1.490, 95%CI: (1.020-2.177)], miliary pulmonary TB [aOR=105.842, 95%CI: (71.704-156.235)], malnutrition [aOR=2.466, 95%CI: (1.110-5.479)]. Additionally, probable TBM was significantly associated with aged < 30 years [aOR=2.174, 95% CI: (1.450-3.261)], aged 30-59 years [aOR=1.670, 95% CI: (1.222-2.282)], farmer [aOR=1.482, 95%CI: (1.203-1.825)], miliary pulmonary TB [aOR=108.696, 95%CI: (87.122-135.613)], digestive system TB [aOR=2.906, 95%CI: (1.762-4.793)]. Conclusion: Aged <30 years, farmer and miliary pulmonary TB were associated with increased probability for TBM among TB patients. Screening TB Patients with above characteristics could facilitate clinicians to identify TBM patients at early stage.